The Dominance of Homeopathic Medicine in Yoruba Healthcare Delivery - Richard Taye Oyelakin (Yoruba Studies Review)
This essay, in the main, argues that the strength and dominance of Yoruba Indigenous Medicine (here-in YIM) consists, not just in outlining the properties of the ingredients, structure, and process of production, as well as modes and mediums of administration, but also, and fundamentally, in the whole qualifying moral and spiritual status of the producers and administrators of the medicine. Further argued that this qualification is what enables YIM to be able to heal rather than cure, where healing is addressing the both physical and spiritual cause(s) and source(s) of the illness. A system of medicine, which prioritizes the sanctity of the dispensers in addition to the drug processes, is considered dominant. Consequently, by being dominant, YIM could help in combating any emerging pandemic, if accorded due recognition. The paper calls for this recognition and development of medicine to enable the world to benefit from it in case of a future and perhaps more deadly outbreak.